High Reactor Configuration and Power Frequency Resonance Analysis for The Cuting-Off of 220 kV Single-Circuit Long Line - Bin CAO; Lifang MIAO; Shuai YUAN (Zhongguo dianli)
In order to avoid overvoltage in the power grid, shunt reactor is usually installed at both ends of long lines. As the power grid construction is expanding, long lines are often cut off and new substations are connected into the grid in order to improve the transmission capacity of grid. In the process, resonant accidents caused by improper configuration of shunt reactor are frequent. Based on PSCAD software, the precise electromagnetic transient model of renewable energy transmission project through 220 kV single-circuit long line is established in this paper. The dynamic characteristics of power frequency resonance and the parameter configuration of the shunt reactor and a small neutral reactor are analyzed. The influence trend of line-to-ground capacitance, line compensation degree and neutral reactor with power frequency resonance are analyzed quantitatively. Finally, the resonance problem is settled successfully with the proposed method, which can provide technical reference and practical experience for the design and operation of power grid.